Bioévaluation De La Qualité Des Eaux Du Cours D’eau Menoua En Zone Périurbaine De Dschang, Ouest Cameroun - Ngameni Tchamadeu Norbert; Patricia Bi Asanga Fai; Mpoame Mbida; Kenko NKontcheu Daniel Brice (European Scientific Journal, ESJ, 2017)
We conducted a study to assess the impact of peri-urban agricultural activities of the city of Dschang on the water quality and macroinvertebrate structure of the Menoua stream. This study covered 3 stations (one reference station at the upstream of the peri-urban agricultural activities and two downstream) with a monthly sampling frequency from March 2015 to February 2016. The physico-chemical analysis were carried out according to standard protocols while the benthic macro-fauna was harvested using a haze net of 30 cm side and 400 μm mesh size. Physico-chemical parameters such as temperature, pH, conductivity, TDS (Total Dissolved Solids), salinity, turbidity, colour, SS (Suspended Solids), nitrate, ammonium and orthophosphate were analyzed. The inventory of benthic macroinvertebrates revealed a taxonomic richness of 42 families and 77 taxa and a gross abundance of 1833 individuals. Spatio-temporal monitoring of physicochemical and biological parameters provided the image of relatively low pollution. Metrics such as total taxonomic richness, richness of ETO (Ephemeroptera-Trichoptera-Odonata), relative abundance of Ephemeroptera-Trichoptera-Odonate (% ETO), diversity of Shannon and Weaver and Pielou's equitability were determined at each of the three stations. These indices, unlike several other studies, increased downstream of anthropogenic activities. Low agricultural activity in the watershed has resulted in habitat diversification and availability of resources for benthic macroinvertebrates, resulting in increased abundance and diversity